2008
DOI: 10.1007/s10803-008-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms in a Sample of Children with Pervasive Developmental Disorders

Abstract: Objective To evaluate gastrointestinal (GI) problems in a large, well-characterized sample of children with pervasive developmental disorders (PDDs). Methods One hundred seventy two children entering one of two trials conducted by the Research Units on Pediatric Psychopharmacology (RUPP) Autism Network were assessed comprehensively prior to starting treatment and classified with regard to GI symptoms. Results Thirty nine (22.7%) were positive for GI problems, primarily constipation and diarrhea. Those with GI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
165
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(182 citation statements)
references
References 35 publications
10
165
0
7
Order By: Relevance
“…In contrast, Wang, Tancredi and Thomas (2011) found that increased autism severity is associated with increased odds of having GI problems. Nikolov et al (2009) also found no difference between those with and without GI problems, based on demographic characteristics or measures of adaptive functioning. Gorrindo, Williams, Lee, Walker, McGrew and Levitt (2012) investigated gastrointestinal symptoms by both clinical evaluation and parental report.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, Wang, Tancredi and Thomas (2011) found that increased autism severity is associated with increased odds of having GI problems. Nikolov et al (2009) also found no difference between those with and without GI problems, based on demographic characteristics or measures of adaptive functioning. Gorrindo, Williams, Lee, Walker, McGrew and Levitt (2012) investigated gastrointestinal symptoms by both clinical evaluation and parental report.…”
mentioning
confidence: 72%
“…There was also no association found between GI symptoms and the Childhood Autism Rating Scale scores. In support, Nikolov, Bearss, Lettinga, Erickson, Rodowski, Aman et al (2009) found that those with gastrointestinal problems were no different from those without gastrointestinal problems in terms of autism symptom severity. Similarly, Molloy and Manning-Courtney (2003) found that frequency of gastrointestinal symptoms did not vary by age, gender, race or severity of autism.…”
mentioning
confidence: 90%
“…Specifically, as reported in the study of Williams et al (2000), the most common factors that parents felt influenced food selectivity were "texture" (69.4%) and "taste" (53.2%). Another hypothesis that has been drawn in order to explain the mechanisms underlying food selectivity in ASD is the relationship between this atypical eating behavior and GI symptoms: food selectivity may be a reason of GI symptoms at least in a part of these individuals (Ibrahim et al, 2009;Nikolov et al, 2009;Whitehouse et al, 2001). In our sample of children with ASD the prevalence of GI symptoms was of 13.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that gastrointestinal (GI) problems are common in ASD and, even though the results are contrasting, food selectivity may contribute to GI problems in a portion of these individuals (Chaidez, Hansen, & Hertz-Picciotto, 2014;Gorrindo et al, 2012;Horvath & Perman, 2002;Ibrahim, Voigt, Katusic, Weaver, & Barbaresi, 2009;Maenner et al, 2012;Mazefsky, Schreiber, Olino, & Minshew, 2014;Mazurek et al, 2013;Mouridsen, Isager, & Rich, 2013;Nikolov et al, 2009;Valicenti-McDermott, McVicar, Cohen, Wershil, & Shinnar, 2008;Whitehouse, Maybery, Wray, & Hickey, 2001). Furthermore, it has been suggested that sensory processing problems, such as sensory sensitivity, which are common among individuals with ASD, could be possible mechanisms underlying food selectivity (Cermack, Curtin, & Bandini, 2010;Mazurek et al, 2013;Suarez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Children with ASD with GI symptoms were no different from children without GI symptoms in demographic characteristics, measures of adaptive functioning or autism symptom severity (Nikolov et al, 2009). However, children with GI symptoms showed greater symptom severity on measures of irritability, anxiety and social withdrawal and were less likely to respond to treatment (Nikolov et al, 2009).…”
mentioning
confidence: 99%